A sex chromosome inversion is associated with copy number variation of mitochondrial DNA in zebra finch sperm. Issue 9 (1st September 2021) - Knief, Ulrich; Forstmeier, Wolfgang; Kempenaers, Bart; Wolf, Jochen B. W.
Abstract : The propulsion of sperm cells via movement of the flagellum is of vital importance for successful fertilization. While the exact mechanism of energy production for this movement varies between species, in avian species energy is thought to come predominantly from the mitochondria located in the sperm midpiece. Larger midpieces may contain more mitochondria, which should enhance the energetic capacity and possibly promote mobility. Due to an inversion polymorphism on their sex chromosome TguZ, zebra finches ( Taeniopygia guttata castanotis ) exhibit large within-species variation in sperm midpiece length, and those sperm with the longest midpieces swim the fastest. Here, we test through quantitative real-time PCR in zebra finch ejaculates whether the inversion genotype has an effect on the copy number of mitochondrial DNA (mtDNA). We find that zebra finches carrying the derived allele (correlated with longer sperm midpieces) have more copies of the mtDNA in their ejaculates than those homozygous for the ancestral allele (shorter midpieces). We suggest downstream effects of mtDNA copy number variation on the rate of adenosine triphosphate production, which in turn may influence sperm swimming speed and fertilization success. Central components of gamete energy metabolism may thus be the proximate cause for a fitness-relevant genetic polymorphism, stabilizing a megabase-scale inversion at an intermediate allele frequency in the wild.